Battery positive electrode active material and preparation method thereof, positive plate and lithium ion battery
By mixing and calcining the NCM ternary material with the Ta element-containing material, the F element-containing material and the conductive polymer, the problem of ion mixing and microcracking of high nickel materials in lithium batteries is solved. The battery cycle performance and first charge and discharge efficiency are significantly improved.
Patent Information
- Application Number
- CN202411671616.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
High-nickel NCM ternary materials are prone to ion mixing and microcracks in lithium batteries, affecting their cycling performance.
通过将NCM三元材料与含Ta元素材料、含F元素材料及导电聚合物混合,并经过高温煅烧制得改性NCM三元材料。
The introduction of modified NCM ternary materials has improved the first charge and discharge efficiency and cycling performance of lithium-ion batteries, and has suppressed the formation of microcracks and ion mixing.
Smart Images

Figure CN119481034A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a battery positive electrode active material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art
[0002] In today's society, the main types of positive electrode materials for lithium batteries are lithium cobalt oxide, NCM ternary materials, and lithium iron phosphate. Among them, NCM ternary materials are favored by battery manufacturers because of their high energy density, and research on them is becoming more and more in-depth.
[0003] At present, NCM ternary materials can be divided into NCM523, NCM622, NCM811 and other types according to the proportion of Ni, Co and Mn. The increase of Ni content is conducive to improving capacity, but high nickel materials in lithium batteries will not only lead to Ni 2+ With Li + Ion mixing occurs, and microcracks will appear after a period of charge and discharge, thus affecting its cycle performance. Therefore, how to improve the stability of high-nickel materials has become a top priority. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems and provide a battery positive electrode active material and a preparation method thereof, a positive electrode sheet and a lithium ion battery.
[0005] To achieve the above purpose, the technical solution provided by the present invention is:
[0006] The first aspect of the present application provides a battery positive electrode active material, which comprises a modified NCM ternary material. The modified NCM ternary material is obtained by modifying the NCM ternary material with a Ta-containing material, a F-containing material and a conductive polymer.
[0007] The NCM ternary material is selected from NCM523, NCM622 or NCM811.
[0008] The Ta element-containing material is selected from at least one of tantalum pentafluoride, tantalum pentachloride and tantalum pentabromide.
[0009] The F-containing material is selected from at least one of tantalum pentafluoride, magnesium fluoride and aluminum fluoride.
[0010] The conductive polymer is selected from at least one of polypyrrole, polydioxythiophene and polyaniline.
[0011] The second aspect of the present application provides a method for preparing a positive electrode active material for a battery, comprising the following steps: uniformly mixing an NCM ternary material with a Ta-containing material, a F-containing material and a conductive polymer, and calcining the mixture to obtain a modified NCM ternary material.
[0012] The calcination temperature is 450-500°C, and the calcination process is carried out under a protective atmosphere; the calcination heating rate is 20-40°C / min, and the calcination annealing rate is 15-25°C / min.
[0013] The molar ratio of the NCM ternary material to the Ta element is in the range of 22-32:1; the molar ratio of the NCM ternary material to the F element is in the range of 215-300:1; and the mass ratio of the NCM ternary material to the conductive polymer is in the range of 39-54:1.
[0014] The third aspect of the present application provides a positive electrode sheet, which contains a battery positive electrode active material provided by the first aspect of the present application or prepared by the method provided by the second aspect of the present application.
[0015] The fourth aspect of the present application provides a lithium-ion battery, which contains the positive electrode sheet provided in the third aspect of the present application.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The invention mixes NCM ternary material, Ta element-containing material, F element-containing material and conductive polymer, and then calcines at high temperature to obtain modified NCM ternary material; the modified NCM ternary material of the invention is used in the positive electrode active material of lithium ion battery to improve the initial charge and discharge efficiency and cycle performance of the battery.
[0018] The introduction of Ta element makes the positive electrode active material particles arranged radially in a needle-like structure perpendicular to the positive electrode surface. This structure reduces the shrinkage and expansion of the positive electrode active material particles during the cycle and inhibits the formation of microcracks. Due to the charge compensation mechanism, F - The addition of Ni 2+ The content of Li + / Ni 2+ The mixing of F - The introduction of the defect of reduced conductivity further improves the conductivity of the material, thereby improving the initial charge and discharge efficiency of the battery; therefore, the battery performance can be greatly improved under the synergistic effect of Ta elements, F elements and conductive polymers.
[0019] The solution of the present invention is particularly suitable for NCM811 materials with high Ni content, can improve the stability of positive electrode materials containing high nickel, and has a significant effect on improving the initial charge and discharge efficiency and cycle performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1: Schematic diagram of the process of preparing modified NCM811 in Example 1 of the present invention.
[0021] Figure 2 : SEM image of the modified NCM811 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.
[0023] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.
[0024] For the sake of simplicity, this document only specifically discloses some numerical values and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.
[0025] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.
[0026] The present application provides a lithium-ion battery positive electrode active material, wherein the battery positive electrode active material comprises a modified NCM ternary material, wherein the modified NCM ternary material is obtained by modifying the NCM ternary material with a Ta-containing material, a F-containing material and a conductive polymer.
[0027] The NCM ternary material in the present application can be selected from but not limited to: NCM523, NCM622 or NCM811.
[0028] The Ta element-containing material in the present application may be selected from but not limited to: at least one of tantalum pentafluoride (TaF5), tantalum pentachloride (TaCl5), and tantalum pentabromide (TaBr5).
[0029] The F-containing material in the present application may be selected from but not limited to: at least one of tantalum pentafluoride (TaF5), magnesium fluoride (MgF2), and aluminum fluoride (AlF3).
[0030] Preferably, the material containing Ta element and the material containing F element can directly adopt tantalum pentafluoride (TaF5).
[0031] The conductive polymer in the present application may be selected from but not limited to: at least one of polypyrrole (PPy), polyaniline (PANi), and polydioxythiophene (PEDOT).
[0032] The present application also provides a method for preparing a positive electrode active material for a battery, comprising the following steps: uniformly mixing an NCM ternary material with a Ta-containing material, a F-containing material and a conductive polymer, and calcining the mixture to obtain a modified NCM ternary material.
[0033] Preferably, the NCM ternary material, the Ta-containing material, the F-containing material and the conductive polymer are mixed by mechanical grinding to form a mixed powder, which is then calcined at a high temperature.
[0034] In some embodiments, the calcination temperature is 450° C.-500° C., and the calcination process is performed under a protective atmosphere; the protective atmosphere in the present application may use nitrogen or other inert gases that do not produce chemical reactions during the calcination process.
[0035] In some embodiments, the heating rate of calcination is 20-40° C. / min, and the annealing rate of calcination is 15-25° C. / min.
[0036] In some embodiments, the molar ratio of the NCM ternary material to the Ta element ranges from 22-32:1; the molar ratio of the NCM ternary material to the F element ranges from 215-300:1; and the mass ratio of the NCM ternary material to the conductive polymer ranges from 39-54:1.
[0037] The present application also provides a positive electrode sheet, which contains the above-mentioned battery positive electrode active material.
[0038] In some embodiments, the positive electrode sheet further contains a conductive agent and a binder; the selection of the mixing ratio of the positive electrode active material to the conductive agent and the binder can be reasonably determined by those skilled in the art through experiments and experience.
[0039] The present application also provides a lithium-ion battery, which contains the above-mentioned positive electrode sheet.
[0040] In some embodiments, the batteries of the present application may be assembled into a battery module. The number of batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0041] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0042] In an electrical device containing the battery of the present application, the battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, aircraft, ships and satellites, energy storage systems, electrical equipment, etc., but is not limited thereto; as an electrical device, the battery can be selected according to its usage requirements.
[0043] The present invention is further described in detail below in conjunction with specific embodiments:
[0044] Embodiment 1:
[0045] 1. Preparation of modified NCM811 material
[0046] A certain amount of NCM811, TaF5 and PEDOT were put into a mortar, ground and mixed until uniform, and then transferred to a magnetic boat. N2 was introduced into a tube furnace and calcined at 450℃-500℃ for 8h to finally obtain modified NCM811. The electron microscope image is shown in the figure below. Figure 1 As shown; wherein, the heating rate is 30°C / min, the annealing rate is 20°C / min; the mass ratio of NCM811 to TaF5 is 30-32:1, and the mass ratio of NCM811 to PEDOT is 45-48:1.
[0047] 2. Preparation of positive electrode slurry:
[0048] The positive electrode active material is NCM811 modified with the product obtained in step 1, the binder is PVDF (KF1100), and the conductive agent is Super P (Swiss Termeco); the mixture is stirred and mixed in a ratio of positive electrode active material: binder: conductive agent = 95.8:2.1:2.1; after mixing evenly, the mixture is coated on a 14um aluminum foil and dried in a vacuum drying oven at 130°C for 12h to obtain a positive electrode sheet with a uniform coating.
[0049] 3. Assembly of button batteries:
[0050] The button battery shell uses CR2032 model, the diaphragm uses 20um diaphragm, and the electrode uses the positive electrode obtained in step 2. In a glove box filled with argon, assemble the button battery in the following order: battery shell - place positive electrode - drip electrolyte - place diaphragm - drip electrolyte - place lithium sheet - place gasket spring - battery shell.
[0051] 4. Test of the first charge and discharge efficiency:
[0052] The button battery was charged and discharged at 0.2C using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A) with a voltage range of 2.7-4.3V. The test results are shown in Table 1.
[0053] 5. Cycle performance test:
[0054] The button battery was charged and discharged for 50 cycles at 0.2C using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A). The voltage range was 2.7-4.3V. The test results are shown in Table 1.
[0055] Embodiment 2:
[0056] It is basically the same as Example 1, except that the mass ratio of NCM811 to TaF5 is 26-28:1.
[0057] Embodiment 3:
[0058] It is basically the same as Example 1, except that the mass ratio of NCM811 to TaF5 is 28-30:1.
[0059] Embodiment 4:
[0060] It is basically the same as Example 1, except that the mass ratio of NCM811 to TaF5 is 32-34:1.
[0061] Embodiment 5:
[0062] It is basically the same as Example 1, except that the mass ratio of NCM811 to TaF5 is 34-36:1.
[0063] Embodiment 6:
[0064] It is basically the same as Example 1, except that the mass ratio of NCM811 to PEDOT is 39-42:1.
[0065] Embodiment 7:
[0066] It is basically the same as Example 1, except that the mass ratio of NCM811 to PEDOT is 42-45:1.
[0067] Embodiment 8:
[0068] It is basically the same as Example 1, except that the mass ratio of NCM811 to PEDOT is 48-51:1.
[0069] Embodiment 9:
[0070] The same as Example 1, except that the mass ratio of NCM811 to PEDOT is 51-54:1.
[0071] The method is basically the same as Example 1, except that TaF5 is not introduced in step 1.
[0072] Comparative Example 2:
[0073] It is basically the same as Example 1, except that: no PEDOT is introduced in step 1.
[0074] Comparative Example 3:
[0075] It is basically the same as Example 1, except that the traditional NCM811 material is used as the positive electrode active material.
[0076] Table 1 Experimental test results of embodiments and comparative examples
[0077] serial number First charge and discharge efficiency at 0.2C 50-cycle capacity retention rate Example 1 93.8% 92.3% Example 2 92.3% 89.1% Example 3 92.7% 89.6% Example 4 92.8% 90.1% Example 5 91.9% 89.3% Example 6 91.1% 87.9% Example 7 92.9% 88.2% Example 8 92.5% 88.8% Example 9 92.0% 88.3% Comparative Example 1 91.1% 84.2% Comparative Example 2 89.2% 86.7% Comparative Example 3 88.9% 83.1%
[0078] The test and evaluation results of each embodiment and comparative example are as follows:
[0079] It can be seen from the above table that the experimental test results of the schemes of Examples 1-9 of the present invention are better than the schemes of Comparative Example 1 without the introduction of TaF5 and Comparative Example 2 without the introduction of PEDOT, and are more significantly better than the scheme of Comparative Example 3 using traditional NCM811 material as the positive electrode active material.
[0080] The positive electrode active material of the embodiment of the present invention adopts modified NCM811 material, wherein the modified NCM811 material not only reduces the shrinkage and expansion degree of the positive electrode active material particles during the cycle process by introducing TaF5 material, inhibits the formation of microcracks, but also inhibits the occurrence of ion mixing phenomenon, thereby improving the cycle performance; the doping of conductive polymer PEDOT can solve the problem of F - The defect of reduced conductivity is introduced to further improve the conductivity of the positive electrode active material, thereby improving the initial charge and discharge efficiency of the battery; the initial charge and discharge efficiency and cycle performance of the embodiment of the present invention are significantly better than those of the comparative example.
[0081] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A positive electrode active material for a battery, characterized in that: The positive electrode active material of the battery comprises a modified NCM ternary material, wherein the modified NCM ternary material is obtained by modifying the NCM ternary material with a Ta-containing material, a F-containing material and a conductive polymer.
2. The positive electrode active material of a battery according to claim 1, characterized in that: The NCM ternary material is selected from NCM523, NCM622 or NCM811.
3. The positive electrode active material of a battery according to claim 1, characterized in that: The Ta-containing material is selected from at least one of tantalum pentafluoride, tantalum pentachloride and tantalum pentabromide.
4. The positive electrode active material of a battery according to claim 1, characterized in that: The F-containing material is selected from at least one of tantalum pentafluoride, magnesium fluoride and aluminum fluoride.
5. The positive electrode active material of a battery according to claim 1, characterized in that: The conductive polymer is selected from at least one of polypyrrole, polydioxythiophene and polyaniline.
6. A method for preparing a positive electrode active material for a battery, characterized in that: The method comprises the following steps: uniformly mixing NCM ternary material, Ta element-containing material, F element-containing material and conductive polymer, and calcining to obtain modified NCM ternary material.
7. The method for preparing a positive electrode active material for a battery according to claim 6, characterized in that: The calcination temperature is 450-500°C, and the calcination process is carried out under a protective atmosphere; the calcination heating rate is 20-40°C / min, and the calcination annealing rate is 15-25°C / min.
8. The method for preparing a positive electrode active material for a battery according to claim 6, characterized in that: The molar ratio of the NCM ternary material to the Ta element is in the range of 22-32:1; the molar ratio of the NCM ternary material to the F element is in the range of 215-300:1; and the mass ratio of the NCM ternary material to the conductive polymer is in the range of 39-54:
1.
9. A positive electrode sheet, characterized in that: The positive electrode sheet contains the battery positive electrode active material described in any one of claims 1 to 5 or prepared by the method described in any one of claims 6 to 8.
10. A lithium ion battery, characterized in that: A lithium-ion battery contains the positive electrode sheet according to claim 9.